Confirmatory and Exploratory Factor Analysis for Validating Allen and Meyer Organizational Commitment Questionnaire for Health Professionals in Ethiopia—Amharic Language - Agegnehu W; Abdissa D; Alemayehu D (Dove Medical Press, 2022)
Wubetu Agegnehu,1 Dinaol Abdissa,1 Dereje Alemayehu1,2 1Department of Public Health, Mizan-Tepi University, Mizan-Aman, Ethiopia; 2Department of Health Economics, Management, and Policy, Jimma University, Jimma, EthiopiaCorrespondence: Wubetu Agegnehu, Email wubetuagegnheu@gmail.comBackground: Ethiopia does not have validated tools for assessing organizational commitment. The aim of this study was to develop an Ethiopian version of the organizational commitment questionnaire (OCQ-Eth) and to evaluate its psychometric properties in the assessment of organizational commitment in healthcare organizations in Ethiopia.Methods: A cross-sectional study was conducted in 14 healthcare facilities of the Bench-Sheko zone. The collected data were entered into EpiData version 3.1. The data were then exported into STATA version 14.1 and SPSS version 22 for analysis. Confirmatory factor analysis and exploratory factor analyses were performed for psychometric evaluation of OCQ in the Ethiopian context.Results: Confirmatory factor analysis showed the original model for organizational commitment did not meet the acceptable model fit. After confirmatory factor analysis, exploratory factor analysis was performed and subsequent confirmatory factor analysis resulted in the development of OCQ-Eth with 16 items classified under four factors (continuance, affective, normative, and concern for the organization) which explained 61.2% of cumulative variance. The three measures of organizational commitment exhibited discriminant and convergent validity. The model fit was improved after exploratory factor analysis.Conclusion: The extracted factor structure exhibited acceptable goodness of fit. The instrument was fit to evaluate the organizational commitment of healthcare professionals of Ethiopia.Keywords: organizational commitment, Amharic language, Ethiopia